The Relationship between Organisational Factors and Job Frustration among Saudi Social Workers - Abdulaziz Albrithen; Nadir A. Yalli (Social Work and Society, 2022)
The relationship between organisational factors (e.g. organisational structure and resources) and job frustration can affect the outcomes of social work in different ways. By using quantitative methodology and social survey (n= 266), this descriptive study aims to analyse the relationship between the organisational factors and the job frustration among social workers which influence the performance of social work roles in Saudi hospitals. The study findings show that job frustration can be determined by the extent to which they perceive clarity in the job and the extent to which they perceive adequate autonomy to carry out their roles.